2021
DOI: 10.1021/acssuschemeng.1c03409
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Size-Controlled in Vivo Biocompatible Immunoglobulin-Based Nanoparticles by a Swift Thermal Formation

Abstract: Protein-based nanoparticles are promising candidates to be used as nanomedicine due to their high biocompatibility. On the other hand, functional nanoagents are fabricated using complex, nonscalable, and environmentally unfriendly procedures. An urge to meet multiple biomedical and industrial requirements highlights a need to find a universal, ecofriendly, and flexible synthetic strategy of functional nanoagent engineering. Here, we show a green, ultrafacile, and size-controlled synthesis (swift thermal format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Several transcytosis-based strategies resulted in excellent tumor specificity but were not included in the analysis because “non-targeted” nanoparticles are not available, for example, for nanoparticles made of the targeting protein itself [ 126 ]. These also include transferrin nanoparticles [ 127 ], albumin nanoparticles [ 128 ], or albumin nanoparticles modified with transferrin [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several transcytosis-based strategies resulted in excellent tumor specificity but were not included in the analysis because “non-targeted” nanoparticles are not available, for example, for nanoparticles made of the targeting protein itself [ 126 ]. These also include transferrin nanoparticles [ 127 ], albumin nanoparticles [ 128 ], or albumin nanoparticles modified with transferrin [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…That causes rapid plasma clearance of the nanocarriers leading to short nanoparticle plasma half-life [102]. Therefore, it is necessary to study in detail the issues related to the factors that affect blood circulation [8,103], as well as elimination [104,105] of nanoparticles for successful applications of in vivo magnetofection, search for new hybrid delivering nanomaterials [106][107][108][109] or implementation of more efficient biochemical binding and targeting techniques [110][111][112][113][114][115][116]. However, we believe that the magnetofection technique can become a solid option for in vivo targeting combined with improved efficacy of gene delivery, potentially in combination with other physical techniques (electroporation, sonoporation) if appropriate magnetic fields can be generated and if an ideal coating of magnetic particles is found.…”
Section: Discussionmentioning
confidence: 99%
“…These nanoparticles are biocompatible and capable of encapsulating other substances, such as nanosized magnetite. Using this method, nanoparticles with various portions of trastuzumab (from 10 to 100%) were obtained [ 121 ]. Imaging flow cytometry assay showed that even NPs with 10% of trastuzumab specifically bind SKBR-3 cells overexpressing receptor HER2 [ 121 ].…”
Section: Protein-based Targeting Self-assembling Nanoparticles For Bi...mentioning
confidence: 99%